The misadventures of memory and the benefits of forgetting.The amnesic remembrance of colombian cinema - Alvarado Duque, Carlos Fernando (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
This article presents a reflection about the tension between memory and forgetting within the colombian cinema. Its interest, following the work of Paul Ricoeur and Marc Augé, is to propose that memory claim different forget’s strategies to shape human experience. Of this form, the film doesn’t work as a story of the past, a place to remember other times, but as a device that determines the present. Memory and forgetting confront on the screen to make the troubled history of a nation understands its own current condition. The films, object of analysis (1960-2010), illustrate the need to remember and the right of the Colombian people to forget.